2021
DOI: 10.1038/s41598-021-83563-9
|View full text |Cite
|
Sign up to set email alerts
|

Delta-9-tetrahydrocannabinol inhibits invasion of HTR8/SVneo human extravillous trophoblast cells and negatively impacts mitochondrial function

Abstract: Prenatal cannabis use is a significant problem and poses important health risks for the developing fetus. The molecular mechanisms underlying these changes are not fully elucidated but are thought to be attributed to delta-9-tetrahydrocannabinol (THC), the main bioactive constituent of cannabis. It has been reported that THC may target the mitochondria in several tissue types, including placental tissue and trophoblast cell lines, and alter their function. In the present study, in response to 48-h THC treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…These observations provide evidence to suggest that genes encoding for HSP70 may be a common downstream target for both glucocorticoid-and THC-mediated signaling. In contrast to speculations derived from the studies of Natale et al (2020), Walker et al (2021) suggested that THC does not buffer subcellular stress signaling through interactions with CB1 and CB2 within the human trophectoderm [24]. They demonstrated that exposure to 20 µM THC significantly increased expression of HSPs 60 and 70, but not antioxidant enzyme mRNA within HTR8/SVneo cells.…”
Section: Effects Of Thc On Glucocorticoid Receptors and Downstream Gene Expressionmentioning
confidence: 82%
See 4 more Smart Citations
“…These observations provide evidence to suggest that genes encoding for HSP70 may be a common downstream target for both glucocorticoid-and THC-mediated signaling. In contrast to speculations derived from the studies of Natale et al (2020), Walker et al (2021) suggested that THC does not buffer subcellular stress signaling through interactions with CB1 and CB2 within the human trophectoderm [24]. They demonstrated that exposure to 20 µM THC significantly increased expression of HSPs 60 and 70, but not antioxidant enzyme mRNA within HTR8/SVneo cells.…”
Section: Effects Of Thc On Glucocorticoid Receptors and Downstream Gene Expressionmentioning
confidence: 82%
“…The successful production and subsequent development of an embryo from competent oocytes is dependent on many factors that are influenced by the ECS. Namely, CB1 receptors have been localized on the outer mitochondrial membrane, suggesting that the ECS regulates the utilization of cellular energy and apoptosis [24,[33][34][35]. The direct roles of the ECS during embryonic development is yet to be fully elucidated; however, multiple studies have suggested that the ECS influences embryo development directly and indirectly by modulating gene expression and mitochondrial processes related to apoptosis and cellular energy balance [23,24,[33][34][35][36].…”
Section: Endocannabinoid System (Ecs)mentioning
confidence: 99%
See 3 more Smart Citations